2022
DOI: 10.1002/adfm.202209769
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Soft‐Structure Functional Surface for Intelligent Liquids’ Distinction, Transportation, and Reaction Mixer

Abstract: Structured surfaces have attracted wide attention because of their great potential in directional transport, liquid collection or separation, microfluidics, etc. However, it remains a big challenge to design a surface that can distinguish various liquids, utilize their inherent properties to control their transportation, and realize functional applications. Herein, it is presented an asymmetric soft-structure functional surface (ASFS) with arrayed curvature units that can make the Laplace pressure as a driving… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 46 publications
(56 reference statements)
0
5
0
Order By: Relevance
“…The combination of active chemical, physical, and geometrical gradients has sparked innovative advances in droplet transport, increasing flexibility, controllability, and speed for a wide range of applications. 32 , 33 , 34 , 35 , 36 This article describes recent achievements in controllable liquid transport on asymmetric two-dimensional (2D) substrates, including two models for droplet sliding and spreading, as well as anisotropic liquid penetration through three-dimensional (3D) Janus membranes. This study also highlights significant advances in the practical applications of liquid-diode materials in several fields, including liquid collection and separation, cargo delivery, bioanalysis, solar-driven water purification, and functional textiles.…”
Section: Introductionmentioning
confidence: 99%
“…The combination of active chemical, physical, and geometrical gradients has sparked innovative advances in droplet transport, increasing flexibility, controllability, and speed for a wide range of applications. 32 , 33 , 34 , 35 , 36 This article describes recent achievements in controllable liquid transport on asymmetric two-dimensional (2D) substrates, including two models for droplet sliding and spreading, as well as anisotropic liquid penetration through three-dimensional (3D) Janus membranes. This study also highlights significant advances in the practical applications of liquid-diode materials in several fields, including liquid collection and separation, cargo delivery, bioanalysis, solar-driven water purification, and functional textiles.…”
Section: Introductionmentioning
confidence: 99%
“…Fog collection techniques have been widely used to address water shortages worldwide. Inspired by the efficient fog collection on the cactus Opuntia microdasys, biomimetic systems have been designed to collect tiny water droplets in foggy conditions. , The asymmetric structures in these designs, which take the form of either two-dimensional (2D) wedge-shaped structures or one-dimensional (1D) conical structures, generate a Laplace pressure difference that propels droplets to move directionally. As a dynamic process, droplet movement is determined by both driving forces and hysteresis acting on the droplet . Strategies to increase the driving forces, such as a constructing grooved rough structure on the cone or modifying the cone with a wettability gradient, have been explored. , However, strategies to reduce interfacial hysteresis encountered by the droplets on the asymmetric 1D cone structure have not been investigated, even though such an operation shows great promise in significantly boosting droplet motion performance.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, multifarious liquid transport strategies have been proposed that rely on the asymmetry of physical structures and surface energy, which generate a directional driving force via breaking the symmetricity of contact line. Typical of them are inspired by living organisms DOI: 10.1002/admi.202300239 including butterfly wings, [11,12] spider silk, [4,[13][14][15][16] cactus, [17][18][19] Nepenthes, [20][21][22][23] Araucaria, [24] or engineering-based design of gradients in topography [25][26][27][28][29][30] and wettability. [31][32][33][34][35] Chen et al [20] reported a continuous and directional water transport on the rim of the pitcher based on the asymmetric multiscale structure.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, multifarious liquid transport strategies have been proposed that rely on the asymmetry of physical structures and surface energy, which generate a directional driving force via breaking the symmetricity of contact line. Typical of them are inspired by living organisms including butterfly wings, [ 11,12 ] spider silk, [ 4,13–16 ] cactus, [ 17–19 ] Nepenthes , [ 20–23 ] Araucaria , [ 24 ] or engineering‐based design of gradients in topography [ 25–30 ] and wettability. [ 31–35 ] Chen et al.…”
Section: Introductionmentioning
confidence: 99%